Neonatal Sequential Organ Failure Assessment Score to Predict Mortality in Neonatal Intensive Care Unit at Tertiary Care Center - KC, Sri Ram; Shah, Ganesh; Chalise, Shiva Prasad; Shrestha, Bijesh; Shrestha, Sailesh; Gautam, Talik; Khanal, Inesh (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: The Neonatal Sequential Organ Failure Assessment (nSOFA) score is a tool used to evaluate degree of organ dysfunction in critically ill neonates admitted to neonatal intensive care units. The nSOFA score is based on respiratory, cardiac and hematological parameters (total score ranges from 0 to 15). This study aims to evaluate the applicability of nSOFA score to predict neonatal mortality in NICU of Patan Academy of Health SciencesMethods: This prospective observational study was conducted at the NICU of Patan Hospital Nepal from May 2023 to November 2024 after ethical clearance from institutional review committee (Reference number: PMP2305231729). The parameters of nSOFA score were recorded at admission and between 48-72 hours of admission. Data were entered in epi-info and analyzed using Easy R software.Results: Among the 134 neonates enrolled, a total of 105(78.40%) survived, while 29(21.60%) died during the study period. At the time of admission, the nSOFA score, using a cutoff value of ≥4, demonstrated a sensitivity of 69% and specificity of 91.40% for predicting mortality. The corresponding positive predictive value (PPV) and negative predictive value (NPV) were 69% and 91.40%, respectively. Within 48 to 72 hours of admission, the predictive performance of the nSOFA score improved, with an area under the curve (AUC) of 0.98 (95% CI: 0.971–1). Using a cutoff of ≥5 during this period yielded a sensitivity of 75.70%, specificity of 99.0%, PPV of 96.60%, and NPV of 91.40%.Conclusions: The nSOFA score is an important tool for predicting neonatal mortality in NICUs and can be used to guide clinical decision-making.